2008
DOI: 10.1177/1088767908319597
|View full text |Cite
|
Sign up to set email alerts
|

Suicides and Suicide Attempts Following Homicide

Abstract: This study used linked, official data for population-based surveillance of homicides, suicides, and homicide–suicides in four U.S. states and four counties. Among 1,503 homicide incidents, less than 5% ( n = 74) were followed by the perpetrator's suicide and 1% ( n = 18) by a nonfatal suicide attempt. However, among men who killed their female intimate partner with a firearm, 59% also took their own life. Homicide–suicide perpetrators did not test positive for an antidepressant more often than other male suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 23 publications
1
29
0
2
Order By: Relevance
“…Studies comparing IPH to IPH followed by a SDA find that employment, education (Gillespie, Hearn, & Silverman, 1998), older age, White race, cohabitation with the victim, and access to a firearm (Barber et al, 2008;Easteal, 1993;Lund & Smorodinsky, 2001) are associated with a higher likelihood of suicide following IPH. Others found that at the time of the homicide, suicidal perpetrators were more likely to be under the influence of drugs and diagnosed with major depression (Bourget, Gagne, & Moamai, 2000).…”
Section: Homicide-suicidementioning
confidence: 99%
See 1 more Smart Citation
“…Studies comparing IPH to IPH followed by a SDA find that employment, education (Gillespie, Hearn, & Silverman, 1998), older age, White race, cohabitation with the victim, and access to a firearm (Barber et al, 2008;Easteal, 1993;Lund & Smorodinsky, 2001) are associated with a higher likelihood of suicide following IPH. Others found that at the time of the homicide, suicidal perpetrators were more likely to be under the influence of drugs and diagnosed with major depression (Bourget, Gagne, & Moamai, 2000).…”
Section: Homicide-suicidementioning
confidence: 99%
“…IPH also has the highest incidence of homicide-suicide of any type of homicide. In addition, IPH followed by a self-destructive act (SDA; for example, suicide or attempted suicide) is almost exclusively committed by men (Barber et al, 2008;Harper & Voigt, 2007;Koziol-McLain et al, 2006;Malphurs & Cohen, 2002;Marzuk, Tardiff, & Hirsch, 1992;Milroy, 1995;Roberts, 2009;Starzomski & Nussbaum, 2000). Men committing lethal SDAs leave little or nothing for scientists to learn about the antecedents of the event without resorting to secondary resources, such as psychological autopsy, for information (Cavanagh, Carson, Sharpe, & Lawrie, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Mannen zijn de voornaamste daders, die hun (ex-)partner doden met een vuurwapen (Barber et al, 2008;Saint-Martin et al, 2007) of steekwapen (Liem & Oberwittler, 2013). Daders van partnerdoding-zelfdodingen zijn ouder dan daders die geen zelfmoord plegen na de doding.…”
Section: 21unclassified
“…Bij een poging heeft de dader weliswaar de intentie om zichzelf van het leven te beroven, maar slaagt hier niet in. Deze definitie volgt diverse internationale studies (Barber et al, 2008;Flynn, et al, 2009). De voor deze studie samengestelde database bestaat uit een aantal bronnen, waarbij de bestaande database Homicide-Suicide 1992-2006 (Liem, 2010;Liem & Koenraadt, 2007) is uitgebreid tot en met 2014, om zo een actueel beeld te kunnen geven.…”
unclassified
“…A qualitative study of adolescents who survived multiple suicide attempts found that vengeance was a commonly cited motive (Orri et al, 2014). Another study found that while fewer than 5% of homicides were followed by suicide, 59% of men who killed their female intimate partner with a firearm took their own lives immediately after (Barber et al, 2008). A study in England and Wales found similar figures for homicide-suicides, but found that in cases where men killed their families and themselves, the suicide was planned prior to the homicide (Milroy, 1998).…”
Section: Motive In Homicide-suicidesmentioning
confidence: 99%